An Analysis of factors influencing ethical compliance in the accounting profession in Kenya - Lyomu, O. (Strathmore University, 2025)
This study investigates the key factors influencing ethical compliance in the accounting profession in Kenya. In recent years, the proliferation of accounting scandals both in Kenya and globally, has drawn increased attention from both practitioners and scholars, highlighting the urgent need to strengthen ethical standards within the profession. This research is motivated by the need to safeguard financial integrity, enhance regulatory effectiveness, and align professional conduct with global ethical benchmarks, within the accounting profession in Kenya. The general objective of the study was to examine the factors that impact ethical compliance among accounting professionals in Kenya. Specifically, the study sought to determine the extent to which gender, firm size, and employee authority level influence ethical compliance. A positivist research philosophy was adopted, relying on quantitative data to test hypotheses and generalize findings. A descriptive research design was employed to analyze the characteristics of the study population and to evaluate relationships between the identified variables. The target population comprised 2,500 members of the Institute of Certified Public Accountants of Kenya (ICPAK) based in Nairobi County. From this, a sample of 250 members was selected, and 220 valid responses were received, yielding a response rate of 88%. Data analysis revealed strong and statistically significant positive correlations between all three independent variables — gender (r = 0.788**), firm size (r = 0.835**), and employee authority level (r = 0.810**) — and ethical compliance. These findings suggest that ethical behavior among accounting professionals is significantly shaped by demographic and organizational factors. The study concludes that ethical compliance must be upheld through concerted efforts by professional bodies, policymakers, and other stakeholders. It recommends strengthening gender equity, supporting ethical practices across firms of varying sizes, and reinforcing ethical awareness at all levels of authority. Despite some limitations, including limited data on respondents' work locations and participant hesitancy due to confidentiality concerns, the study offers important insights into the ethical dynamics of Kenya’s accounting profession. The findings are expected to inform ethical education, governance practices, and policy development within the field.
Full - text thesis